1998
DOI: 10.1902/jop.1998.69.1.62
|View full text |Cite
|
Sign up to set email alerts
|

An Immunocytochemical Study for Lysosomal Cathepsins B and D Related to the Intracellular Degradation of Titanium at the Bone‐Titanium Interface

Abstract: The morphological relationship between titanium and lysosomal proteinases, cathepsins B and D, at the bone-titanium interface using titanium-coated plastic implants placed for 28 days in the tibiae of 6-week-old rats was immunocytochemically investigated by the colloidal immunogold-silver method. Under light microscopy the titanium layer appeared to make direct contact with the bone and one or a few layers of slender cells were interposed between the bone and titanium. Ultrastructurally, the titanium came in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…This experimental method is considered to be a superior technique. However, the number of reports using this technique is even smaller, and there are variabilities in the properties of thin titanium film among reports 17–25 . Okamatsu and colleagues 17 coated titanium using the DC magnetron sputtering method.…”
Section: Discussionmentioning
confidence: 99%
“…This experimental method is considered to be a superior technique. However, the number of reports using this technique is even smaller, and there are variabilities in the properties of thin titanium film among reports 17–25 . Okamatsu and colleagues 17 coated titanium using the DC magnetron sputtering method.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were obtained 4 weeks after implant placement to obtain detailed observation of the titanium‐bone interface after achieving osseointegration, because several investigators reported the successful osseointegration 4 to 12 weeks after implant placement 18–23,25,26 …”
Section: Methodsmentioning
confidence: 99%
“…A method of coating a thin film of titanium on plastic has been used in order to examine an intact titanium‐bone interface. However, there have been only a few such reports in the past 20 years 18–23 . In addition, opinions in these reports have not necessarily been consistent regarding the existence of an amorphous layer at the titanium‐bone interface and the response of surrounding tissue.…”
mentioning
confidence: 99%
“…The results have shown that rapid, strong osseointegration can be achieved with implants having surface roughness in the order of Sa=2 μm [1][2][3] . However, since the implant body is metal, tissue samples cannot readily be prepared, and, therefore, the tissue reaction at the titanium-bone interface cannot be easily evaluated 9,[13][14][15] .…”
Section: Discussionmentioning
confidence: 99%